The Association Between Low Socioeconomic Status With High Physical Limitations and Low Illness Self‐Perception in Patients With Juvenile Idiopathic Arthritis: Results From the Childhood Arthritis Prospective Study1. Issue 3 (March 2015) - Verstappen, Suzanne M. M.; Cobb, Joanna; Foster, Helen E.; Fu, Bo; Baildam, Eileen; Wedderburn, Lucy R.; Davidson, Joyce E.; Ioannou, John; Chieng, Alice; Hyrich, Kimme L.; Thomson, Wendy
<x xml:space="preserve">Abstract</x> Objective To examine the association between socioeconomic status (SES) and delay to a pediatric rheumatology clinic, disease severity, and illness perception in patients with juvenile idiopathic arthritis in England. Methods Using the Index of Multiple Deprivation, 923 consecutive children from the Childhood Arthritis Prospective Study were assigned to SES groups: high‐SES (19.1%), middle‐SES (44.5%), or low‐SES (36.4%). At baseline, disease activity was assessed, and the Childhood Health Assessment Questionnaire (C‐HAQ), the Illness Perception Questionnaire, and the Child Health Questionnaire, version Parent Form 50, were completed. Linear median regression analyses or zero‐inflated negative binominal (ZINB) regression analyses were used. Results Delay to first pediatric rheumatology consultation was the same between the 3 SES groups. Although disease activity scores assessed by the pediatric rheumatologist did not differ between the 3 SES groups, persons in the low‐SES group recorded higher C‐HAQ scores compared to the high‐SES group (zero‐inflated part of ZINB odds ratio 0.28 [95% confidence interval (95% CI) 0.14, 0.55], count part of ZINB β 0.26 [95% CI 0.05, 0.48]). Parents with low SES also reported more often that their children's school work or activities with friends had been limited. Furthermore, the low‐SES group had a worse perception about the consequences of the disease and the effect of treatment than those in the high‐SES group. Conclusion Patients from a low‐SES background report more problems with daily activities and have a lower perception of the consequences of the disease than patients from a high‐SES background, warranting special attention from a multidisciplinary team.